The Effect of Sales Promotion, E-Service Quality, and Price on Impulse Buying in The Shopee Application (Case Study on Shopee Consumers in Jakarta) - Arthur Joshua; Rosali Sembiring (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The trend of e-commerce users in Indonesia has grown quite large in recent years. One of the major E-Commerce in Indonesia is Shopee, Shopee is the first leader in the number of e-commerce visits in Indonesia during the pandemic starting from October to December 2021 with a total number of visitors of 93.4 million visits/month or 33.7 % percentage of traffic share. This research with a quantitative approach aims to determine, prove and analyze the effect of sales promotion, e-service quality and price on impulse buying for Shopee consumers in Jakarta. By using purposive sampling method, the number of samples in this study was 110 respondents. Descriptive analysis techniques and partial least squares inferential analysis were used in this study to analyze the data that had been collected by distributing questionnaires. The significance level was set at 5%, and the SmartPLS software (V.3.30) was used to process and analyze the data. The research results show that: (1) Sales promotion has a positive and significant influence on impulse buying with a path coefficient of 0.697. (2) E-Service Quality has a positive and significant influence on impulse buying with a path coefficient of 0.453. (3) Price has a positive and significant influence on impulse buying with a path coefficient of 0.281. As for sales promotion, e-service quality and price together, they contributed to impulse buying by 0.681 or 68.1%, while the remaining 12.3% was due to other factors outside this research model.